Neurological late-onset lupus associated with cerebrovascular accident in the elderly: Case report and rapid systematic review - Montoya, Karla Giovanna (2022)
Background: Late-onset Systemic Lupus Erythematosus (SLE) is rare and affects older adults. Case report: A 71-year-old woman is reported with generalized weakness and muscle strength loss, which increased suddenly after a hemorrhagic stroke. The patient presented a torpid evolution for six months. The diagnosis of late-onset SLE was confirmed with antinuclear antibodies (+) and compliance with criteria for SLE and neurolupus, with significant improvement after two weeks of treatment. We made a rapid systematic review and found few similar cases with peripheral neuropathy. Conclusion: It is necessary to consider late-onset SLE with peripheral neuropathy in older adults with muscle weakness, as an atypical clinical presentation and the need for confirmatory tests.